STRATEGI PENGEMBANGAN TERNAK DOMBA DI PETERNAKAN DONBA ENGGAR KECAMATAN PARE KABUPATEN KEDIRI - Choirina, Vifi Nurul; Setiyadi, Heru; Primadito, Moh. Raihan Aditya (Universitas Tribhuwana Tunggadewi, 2025)
Sheep farming is widely practiced in Indonesia, but most operations remain small-scale and traditional. Donba Enggar Farm, located in Pare District, Kediri Regency, represents a modern sheep farming enterprise with 150 heads and improved management practices. This study aims to formulate development strategies for the farm to enhance competitiveness and sustainability. Research was conducted using a case study approach with SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis and the Quantitative Strategic Planning Matrix (QSPM). The results place Donba Enggar Farm in Quadrant I of the SWOT diagram, indicating a favorable and aggressive growth position. Five alternative strategies were identified: maintaining production quality, optimizing digital marketing through online platforms, developing organic feed and fertilizer businesses, expanding the flock population, and participating in livestock technology training. Among these, maintaining production quality ranked as the top strategic priority. Overall, the findings highlight that proactive and integrated development strategies can strengthen the farm’s role in meeting the growing demand for sheep, particularly for religious and culinary purposes.